Evaluation structural diversity of Carpinus betulus stand in Golestan Province, North of Iran - VAHAB SOHRABI; RAMIN RAHMANI; SHAHROKH JABBARI; HADI MOAYERI (Smujo International, 2011)
Abstract. Sohrabi V, Rahmani R, Jabbari S, Moayeri H. 2011. Evaluation structural diversity of Carpinus betulus stands in Golestan Province, Northern Iran. Nusantara Bioscience 3: 23-27. In order to investigate structural diversity of Carpinus betulus type in Golestan province, 30 modified Whittaker plots by systematic random system were located. Per plot, the characteristic of trees and shrubs species (Species name, diameter, and height of trees) are recorded. The heterogeneity indices of Simpson, Shannon–Wiener, Simpson’s reciprocal and number of equally common species were used for the quantitative data. Toward better understand from diversity condition in horizontal and vertical composition of stand, the diameter divided in 10 cm classes and Method of Mohajer and the height divided in 10 m height classes and dominant height, then number of diversity of each class extracted by Ecological Methodology software V.7. The results showed with increase of diameter and height classes, decrease species diversity. Also regeneration layers diversity has significant difference with trees layers. Thus, the study of biodiversity changes in different diameter and height category cause ecologically precise perspective in management of forest stands.